Program Nuklir Iran dan Ketegangan dengan Amerika Serikat: Analisis Geopolitik dan Implikasi terhadap Stabilitas Timur Tengah - Eugenia Kana Daniela Timang Seran; Atika Puspita Marzaman (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study investigates the geopolitical shifts that have occurred between Iran and the United States over Iran’s nuclear program and how they have impacted the stability of the Middle East region. The background of this study is the long-standing tensions caused by the United States’ suspicions about Iran’s nuclear ambitions. These suspicions triggered the JCPOA agreement in 2015 and worsened after the United States withdrew from the JCPOA in 2018. This study aims to gain an understanding of the ways in which strategic geography, threat perceptions, and foreign policy contribute to instability in the region. This study was conducted qualitatively using a descriptive-analytical approach and secondary data obtained from journals, policy reports, and international institutions. The results show that Iran uses its geographic position and support for non-state actors as strategic tools. While the United States pressures Iran through sanctions and military alliances, it also uses its geographic position. These tensions endanger security and destabilize the region. These results are important because they demonstrate the impact of regional nuclear conflicts around the world and suggest that inclusive multilateral diplomacy is needed to resolve conflicts.